EARLY MORTALITY IN NEW PATIENTS ON TREATMENT FOR SMEAR POSITIVE PULMONARY TUBERCULOSIS IN YAOUNDE-CAMEROON - KUABAN, Christopher; Pefura, E; Bava, D; Onana, I (HEALTH SCIENCES AND DISEASE, 2013)
Setting : Tuberculosis centre ofHôpital Jamot, Yaoundé, Cameroon. Objective: - Identify simple clinical determinants associated with early death in hospitalized patients with new smear positive pulmonary tuberculosis (PTB). Design: - A prospective cohort of 501 patients aged ≥ 15 years consecutively admitted from April 2009 to March 2010 was followed up in hospital during the 2-month intensive phase of treatment. On admission, patients were interviewed, their admission chest x-rays read and laboratory tests performed. Deaths occurring between admission and the end of the first 2 months of treatment were recorded as early deaths. Results: - Of the 501patients with a mean age of 35.5 (range: 15-72) years, 59.1% were males and 160 (31.9%) were HIV positive. Twenty-one (4.2%, 95% CI: 2.4-5.9%) eventually died in hospital. Logistic regression analysis showed age ≥ 40 years (OR=3.64, 95% CI: 1.37- 9.67), HIV infection (OR=12.8, 95% CI: 2.74-59.46), anaemia (OR=3.64, 95% CI: 1.09-8.31) and hypoalbuminaemia (OR=3.18, 95% CI: 1.19-8.55) were independent predictors of early death. Conclusion: Our results highlight the importance for the early detection and treatment of HIV infection in these patients. They also emphasize the need of measuring their serum albumin and haemoglobin levels in our environment as they are indicators of prognosis for which specific interventions could improve outcomes.